Biodiversity and structure of ground beetle assemblages (Coleoptera Carabidae) in Bt coro and its effects on non target insects (Bollettino di zoologia agraria e bachicoltura, 2024)
During the years 1997-1998 an in-field evaluation was made of theeffects of transgenic corn on non-target arthropods and on soil fauna. ColeopteraCarabidae, typical soil fauna, were studied and a comparison made of theircommunity structures and degree of specific biodiversity in transgenic and isogeniccorn crops. The taxa normally present on corn plants, particularly Aphididae andCicadellidae, Aranea and Coleoptera (Chrysomelidae, Coccinelidae,Staphilinidae), and other insects living in dose contact with these or with theEuropean Corn Borer (Ostrinia nubilalis), such as Hymenoptera parasitoids andDiptera Syrphidae, were considered as aerial fauna.The statistica} analyses revealed no significant differences in the abundance of thenon-target entomofauna in isogenic corn and transgenic corn. The ground beetleassemblages were quite similar, and any differences appeared to have nocorrelation with the presence of Bt maize. The biodiversity of the Carabidaecommunities was quite low for both types of crops and, on comparing the twotypes of hybrid corn crops, no significant differences were found in any of theindices analysed.
Keywords: Bt corn; non target insects; Carabidae; species diversity; dominance; biodiversity indices